Cross-transmission of resistant gastrointestinal nematodes between wildlife and transhumant sheep - Beaumelle, Camille; Toïgo, Carole; Papet, Rodolphe; Benabed, Slimania; Beurier, Mathieu; Bordes, Léa; Brignone, Anaïs; Curt-Grand-Gaudin, Nadine; Garel, Mathieu; Ginot, Justine; Jacquiet, Philippe; Miquel, Christian; et al. (Peer Community Journal, 2024)

(untitled)
Wild and domestic ungulates can be infected with the same species of gastrointestinal parasitic nematodes. These parasites have free-living stages in the environment that contribute to the ease of transmission among different host species. In addition, gastrointestinal nematodes have developed resistance to anthelmintics which is now considered a major problem for the livestock sector. In a context where wild and domestic ungulates share the same pastures, the maintenance and circulation of resistant gastrointestinal nematodes between species have rarely been explored. In the European Alps, domestic sheep are driven to high-altitude summer pastures and live in sympatry with wild ungulates for several months each year. In this study, we investigated the nemabiome of domestic sheep and Alpine ibex, Capra ibex, in three different areas of the French Alps to evaluate parasite circulation between the two host species. The Alpine ibex is a protected mountain ungulate that is phylogenetically related to sheep and hosts nematode species common to sheep. Using internal transcribed spacer 2 (ITS-2) nemabiome metabarcoding, we found sheep and ibex share similar gastrointestinal nematodes, except for a few species such as Marshallagia marshalli and Trichostrongylus axei. This suggests that the long-term co-occurrence of sheep and ibex on mountain pastures has promoted the exchange of gastrointestinal nematodes between the two hosts. Based on the sequencing of the isotype 1 of the beta tubulin gene, associated with benzimidazole resistance, we found resistant nematodes in all sheep flocks and in all ibex populations. Our results demonstrated that ibex can host and shed resistant strains before transhumant sheep arrive on pastures, and thus could act as a refuge or even contribute to maintaining resistant gastrointestinal nematodes. The relative role of ibex in the maintenance and circulation of resistant strains in sheep remain to be determined.